Determinants of poverty - binary logit model with interaction terms approach - Dudek, Hanna; Lisicka, Iga (Determinanty ubóstwa – podejście wykorzystujące binarne modele logitowe z interakcjami, 2013)
The problem of monetary aspect of welfare in employees’ household was undertaken in this paper. In order to identify the households in danger of poverty, the binary logit models approach was applied. It was found that the estimation of models without the interaction terms results in misspecification error. Due to this, the interaction terms, betweenthe socio-economic factors of households were included in the model. The obtained results can have significant importance in the aspect of social policy in Poland.
Ekonometria = Econometrics, 2013, Nr 3 (41), s. 65-77
Keywords: poverty; household; logit model; interactions; ubóstwo; gospodarstwo domowe; model logitowy; interakcje